Genomes of all known members of a Plasmodium subgenus reveal paths to virulent human malaria - Otto, T.D.; Gilabert, A.; Crellen, T.; Böhme, U.; Arnathau, C.; Sanders, M.; Oyola, Samuel O.; Okouga, A.P.; Boundenga, L.; Willaume, E.; Ngoubangoye, B.; Moukodoum, N.D.; et al. (Springer, 2018)
Plasmodium falciparum, the most virulent agent of human malaria, shares a recent 26 common ancestor with the gorilla parasite P. praefalciparum. Little is known about the other gorilla 27 and chimpanzee-infecting species in the same (Laverania) subgenus as P. falciparum but none of 28 them are capable of establishing repeated infection and transmission in humans. To elucidate 29 underlying mechanisms and the evolutionary history of this subgenus, we have generated multiple 30 genomes from all known Laverania species. The completeness of our dataset allows us to conclude 31 that interspecific gene transfers as well as convergent evolution were important in the evolution of 32 these species. Striking copy number and structural variations were observed within gene families 33 and one, stevor shows a host specific sequence pattern. The complete genome sequence of the 34 closest ancestor of P. falciparum enables us to estimate confidently for the first time the timing of 35 the beginning of speciation to be 40,000-60,000 years ago followed by a population bottleneck 36 around 4,000-6,000 years ago. Our data allow us also to search in detail for the features of P. 37 falciparum that made it the only member of the Laverania able to infect and spread in humans.